Spectroscopic measurement of associating and solvating binary mixtures for the determination of monomer fraction data towards thermodynamic model improvement - Burgess, Aiden Edward (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.